2011
DOI: 10.1097/shk.0b013e3182115f40
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Levels of Peroxiredoxin 4 as a Novel Biomarker of Oxidative Stress in Patients with Sepsis

Abstract: Oxidative stress, a situation with increased reactive oxygen species production and/or decreased antioxidant defense mechanisms, is evident in the pathogenesis of sepsis. Peroxiredoxin 4 (Prx4) is a hydrogen peroxide degrading peroxidase recently found circulating in blood of septic patients and potentially reflecting an antioxidant system in imbalance. We studied Prx4 serum levels of 79 consecutively enrolled medical intensive care unit patients. The diagnostic and prognostic performance of Prx4 was compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 36 publications
4
42
0
3
Order By: Relevance
“…Our current model is further supported by findings that another peroxiredoxin, Prdx4, (the only known secretory member of the peroxiredoxin superfamily) was suggested as a “novel biomarker of oxidative stress in patients with “sepsis shock” [31] and this may be an indication of the general involvement of the peroxiredoxins in diseases that are linked with the “compartmentalized” antioxidant protection. Our discovery of Prdx6 in CSF fits well with this concept; however, the actual mechanism of how this enzyme is trafficked in CSF remains unclear.…”
Section: Discussionsupporting
confidence: 79%
“…Our current model is further supported by findings that another peroxiredoxin, Prdx4, (the only known secretory member of the peroxiredoxin superfamily) was suggested as a “novel biomarker of oxidative stress in patients with “sepsis shock” [31] and this may be an indication of the general involvement of the peroxiredoxins in diseases that are linked with the “compartmentalized” antioxidant protection. Our discovery of Prdx6 in CSF fits well with this concept; however, the actual mechanism of how this enzyme is trafficked in CSF remains unclear.…”
Section: Discussionsupporting
confidence: 79%
“…P<0.05 is statistically significant HbA 1c glycosylated hemoglobin, HOMA IR insulin resistance index, ESR erythrocyte sedimentation rate, ICAM-1 cellular adhesion molecule-1, VCAM-1 vascular cellular adhesion molecule-1, ND non-detectable, NS non-significant members of the peroxiredoxin family and demonstrated that circulating levels of PRDX1, 2, 4, and 6 are markedly raised in diabetic patients with PAD. Although little is known about the pathophysiological role of peroxiredoxins, there is an evidence that they are upregulated in conditions of increased ROS generation (Bast et al 2002;Schulte et al 2011), which supports our observation. Previous reports showed that exposure of cells to oxidative stress and heat shock induced chaperone function of PRDXs, in order to enhance cellular resistance to stressful stimuli (Jang et al 2004).…”
Section: Parametersupporting
confidence: 80%
“…It is a hydrogen peroxide degrading peroxidase recently found circulating in blood of septic patients and potentially reflecting an antioxidant system in imbalance (Schulte et al 2011), similar to atherosclerosis (Madamanchi et al 2005). The amount of secreted PRDX4 is most likely proportional to the initial intracellular expression levels (Okado-Matsumoto et al 2000).…”
Section: Parametermentioning
confidence: 99%
“…Peroxiredoxin 4 is a major anti-oxidative enzyme in the peroxiredoxin family, which has been used as an oxidative stress biomarker in chronic diseases such as cancers [53, 54]. In line with increased SOD production, both catalase and peroxiredoxin 4 were increased in the ileum of MO offspring.…”
Section: Discussionmentioning
confidence: 99%